Factors associated with suicide idea in adolescence: an integrative review - Arielly Tamara Medeiros Nava, Hariane Freitas Rocha Almeida, Rafael Mondego Fontenele, Aline Sharlon Maciel Batista Ramos, Denise Carneiro Machado Cortez, Mayara Moura Luz Monteiro (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/2238-7234.8266-73